Photic stress on coral reefs in the Maldives: The Amphistegina bleaching index. (June 2020) - Stainbank, Stephanie; Spezzaferri, Silvia; Beccari, Valentina; Hallock, Pamela; Adams, Arthur; Angeloz, Aurelie; Basso, Daniela; Caragnano, Annalisa; Del Piero, Nicolo; Dietsche, Patrick; Eymard, Ines; Farley, Nicholas; et al.
Highlights: The ABI is a useful indicator of photo-inhibitory stress within coral reef environments. The utilisation of the ABI, to forecast bleaching events within the Maldivian reefs, is verified. The ABI would be a complementary component to existing and new coral reef monitoring programs. Abstract: The Amphistegina Bleaching Index (ABI) was applied to three Maldivian reefs in the Rasdhoo and North Ari Atolls in 2018, during normal sea surface temperature conditions. This dataset was then compared with a 2015, pre-coral bleaching study. The results provide a context for the verification and application of the ABI in outlining the photo-inhibitory stress status of coral reefs outside of the Florida Reef Tract where it was originally developed. The sampling periods encompass different seasons and temperature regimes. The 2015 field sampling preceeded the El Niño induced, mass coral-bleaching events of 2015 and 2016. It was carried out in late April and early May, during the dry season, when temperatures exceeded 31.5 °C and photosynthetically active radiation (PAR) was high. The 2018 sampling took place near the September equinox, towards the end of the monsoon, when PAR was again high, though water temperatures were 30 °C. Although there were slightly higher percentages of bleached Amphistegina in 2018, there were also higher percentages of juveniles, indicating either that (1) the chronic stress was insufficient to impact asexual reproduction or (2) the onset of stress was within the past few weeks; the latter hypothesis was supported by an increase in PAR and temperature coinciding with the time of sampling. From the ABI plots it is possible to distinguish between the 2015 (high data scatter), highly stressed pre-bleaching conditions with elevated photo-oxidative stress levels, and the near-baseline conditions represented by the 2018 dataset (tight data clustering). Overall, this study thus shows the potential of Amphistegina populations and the ABI in forecasting bleaching events, and contributing to the question of the resilience potential of the coral reefs as a whole. It also highlights the usefulness and suitability of the ABI, within Maldivian coral reefs, as an indicator of photo-inhibition through photo-oxidative stress that can increase susceptibility to coral bleaching as water temperatures approach or exceed the bleaching threshold.